A statistically sound model for astrometric uncertainties to improve minor planet orbit accuracies - Spoto, F. (2025)
Astrometric uncertainties are central to any orbit-fitting procedure. The result of a fit is a nominal solution, which represents the single orbit that best matches the observations, and a confidence region describing the orbital uncertainty, which includes the set of orbital elements statistically compatible with the data and the error model. For well-observed asteroids, the region is well approximated by a multidimensional ellipsoid. In contrast, for short-arc objects (e.g. objects on the NEO Confirmation Page), the uncertainty region appears as a cloud of admissible orbits.